Analysis of nicotinamide N-methyltransferase in oral malignant melanoma and potential prognostic significance. Issue 2 (April 2019) - Mascitti, Marco; Santarelli, Andrea; Sartini, Davide; Rubini, Corrado; Colella, Giuseppe; Salvolini, Eleonora; Ganzetti, Giulia; Offidani, Annamaria; Emanuelli, Monica
Abstract : Oral malignant melanoma (OMM) is an aggressive tumour, and shows deep tissue invasion at initial presentation. The prognosis is worse than that for cutaneous melanoma (CM), and the overall 5-year survival rate is 10–25%. A study of the molecular mechanisms involved in the development of OMM is necessary to identify new prognostic markers. In this study, we evaluated the possible role of nicotinamide N -methyltransferase (NNMT) in OMM. We carried out immunohistochemical analyses to evaluate the expression of NNMT in 15 OMM and 15 CM, measuring the percentage of positive cells and the value of NNMT expression intensity. Furthermore, we explored the relationship between NNMT levels and the prognostic parameters of patients with OMM. NNMT was significantly more expressed in CM compared with OMM, whereas higher staining intensity for NNMT was observed in OMM cases ( P <0.05). In addition, a significant relationship was found between NNMT staining intensity and the presence of ulceration ( P <0.05). Furthermore, univariate analysis showed a negative effect of NNMT expression on the disease-free survival rate ( P <0.05). This study is the first to report the expression of NNMT in OMM and to compare OMM enzyme levels with those detected in CM. Data obtained seem to suggest the presence of potential molecular differences between these two tumours.